Pengembangan E-Book Interaktif Berbasis Canva pada Materi Akhlak-Ku Kelas VI MIS Hidayatul Ilmi Kalitata Kabupaten Luwu Utara - S, Ilham Ramadhan; Marwiyah, St; Rahmadani, Ervi (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
This research discusses the development of a Canva-based interactive e-book for my morals material in class VI MIS Hidayatul Ilmi Kalitata. The research uses a Research and Development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The subjects are class VI students of MIS Hidayatul Ilmi Kalitata for the 2023/2024 academic year. Data was collected through observation, questionnaires and interviews, then analyzed descriptively qualitatively and descriptively quantitatively. The research results show that this Canva-based interactive e-book is valid with a high score, namely 90.90% by media experts, 85.71% by material experts, and 91.66% by language experts. In terms of practicality, this e-book was also rated highly by teachers (82.8%) and students (83.8%). Thus, this interactive e-book is suitable for use in the process of learning my morals material at the school. This research contributes to developing teaching materials that are more interactive and relevant to technological developments, as well as providing empirical evidence regarding the validity and practicality of their use in the learning context of class VI MIS Hidayatul Ilmi Kalitata.